Sleep disturbance as detected by actigraphy in pre-pubertal juvenile monkeys receiving therapeutic doses of fluoxetine - Golub, Mari S. (Neurotoxicol Teratol, 2016)
Sleep disturbance is a reported side effect of antidepressant drugs in children. Using a nonhuman primate model of childhood selective serotonin reuptake inhibitor (SSRI) therapy, sleep was studied quantitatively with actigraphy. Two 48-h sessions were recorded in the home cage environment of juvenile male rhesus monkeys at two and three years of age, after one and two years of treatment with a therapeutic dose of the SSRI fluoxetine, and compared to vehicle treated controls. A third session was conducted one year after discontinuation of treatment at four years of age. During treatment, the fluoxetine group demonstrated sleep fragmentation as indexed by a greater number of rest-activity transitions compared to controls. In addition fluoxetine led to more inactivity during the day as indexed by longer duration of rest periods and the reduced activity during these periods. The fluoxetine effect on sleep fragmentation, but not on daytime rest, was modified by the monkey’s genotype for polymorphisms of monoamine oxidase A (MAOA), an enzyme that metabolizes serotonin. After treatment, the fluoxetine effect on nighttime rest-activity transitions persisted, but daytime activity was not affected. The demonstration in this nonhuman primate model of sleep disturbance in connection with fluoxetine treatment and specific genetic polymorphisms, and in the absence of diagnosed psychopathology, can help inform use of this drug in children.